Predictive Factors of Organ Involvement in Childhood Henoch-Schonlein Purpura - Esra Nagehan Akyol Önder; Pelin Ertan (Galenos Publishing House, 2022)
Objective: Henoch-Schonlein purpura (HSP) is the most common vasculitis of childhood, presenting with immunoglobulin A-dominant immune deposits. Unless there is an organ involvement, the prognosis of HSP is excellent. In this study, we aimed to evaluate clinical and laboratory risk factors for organ involvement in patients with HSP. Method: Our study sample consisted of 95 children with HSP and 75 healthy controls. Clinical and laboratory parameters recorded at the first admission to the hospital were retrospectively evaluated. The neutrophil-tolymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated based on the complete blood counts. Results: Leucocyte, neutrophil and lymphocyte counts, C-reactive protein, PLR, platelet distribution width, and NLR were significantly higher in the HSP group than in the control group (p=0.008, p<0.001, p=0.003, p<0.001, p=0.002, p<0.001, p=0.002, and p<0.001, respectively). In the HSP group, NLR, PLR and lymphocyte were significantly higher among the patients with renal involvement and those with gastrointestinal involvement. Neutrophil levels were correlated with renal involvement. Additionally, the older age onset of the disease and elevated antistreptolysin O (ASO) levels were associated with renal involvement. Conclusion: NLR, PLR and lymphocyte counts may be used as inflammatory indicators of renal and gastrointestinal involvement in HSP. In addition, the neutrophil count is associated with renal involvement. The older age onset of HSP and elevated ASO levels are risk factors for renal involvement in HSP.